2014
DOI: 10.1177/0004563214528882
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative status and the severity of clinical symptoms in patients with post-traumatic stress disorder

Abstract: Background: The aim of this study was to measure the parameters of oxidative stress in the blood of patients with post-traumatic stress disorder. Methods: The study included 80 male war veterans who participated actively in the Homeland war in Croatia. Volunteers were divided into two groups: 50 veterans diagnosed with post-traumatic stress disorder and 30 without diagnosis. The self-assessment Hospital Anxiety and Depression Scale and the Beck Depression Inventory were used to detect the severity of depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
(65 reference statements)
1
18
0
1
Order By: Relevance
“…The only statistically significant difference was diminished concentrations in PTSD of protein carbonyl (an oxidation by-product), but this finding did not adequately separate groups through receiver operating curve analyses, calling into question the clinical importance of the observed differences. Borovac Stefanovic et al (47) studied Croatian war Veterans (50 with PTSD and 30 without PTSD); there were no group differences in serum malondialdehyde (an oxidation by-product), but the PTSD group had lower blood concentrations of erythrocyte superoxide dismutase and erythrocyte glutathione peroxidase, suggesting impaired antioxidant capacity and increased oxidative stress in the PTSD subjects. As part of a magnetic resonance spectroscopy (MRS) study, Michaels et al (48) examined the dorsolateral prefrontal cortex and anterior cingulate cortex among 29 trauma-exposed individuals (12 with PTSD and 17 without PTSD), and found those with PTSD had significantly higher levels of the antioxidant, glutathione in both regions, which may represent a compensatory reaction to increased oxidation (it may also represent an excess of antioxidant activity for unclear reasons).…”
Section: Resultsmentioning
confidence: 99%
“…The only statistically significant difference was diminished concentrations in PTSD of protein carbonyl (an oxidation by-product), but this finding did not adequately separate groups through receiver operating curve analyses, calling into question the clinical importance of the observed differences. Borovac Stefanovic et al (47) studied Croatian war Veterans (50 with PTSD and 30 without PTSD); there were no group differences in serum malondialdehyde (an oxidation by-product), but the PTSD group had lower blood concentrations of erythrocyte superoxide dismutase and erythrocyte glutathione peroxidase, suggesting impaired antioxidant capacity and increased oxidative stress in the PTSD subjects. As part of a magnetic resonance spectroscopy (MRS) study, Michaels et al (48) examined the dorsolateral prefrontal cortex and anterior cingulate cortex among 29 trauma-exposed individuals (12 with PTSD and 17 without PTSD), and found those with PTSD had significantly higher levels of the antioxidant, glutathione in both regions, which may represent a compensatory reaction to increased oxidation (it may also represent an excess of antioxidant activity for unclear reasons).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Atli et al 13 reported elevated levels of serum lipid peroxidation (reflecting the breakdown and oxidation of polyunsaturated fatty acids) and depleted antioxidant enzymes in earthquake survivors with PTSD compared to earthquake-exposed controls. Similarly, Stefanovic et al 14 measured blood levels of SOD and glutathione transferase in Croatian war veterans and found depleted levels of both antioxidants in veterans with PTSD compared to controls. Gene expression studies have found similar alterations in antioxidant gene RNA transcription in patients with PTSD.…”
Section: Introductionmentioning
confidence: 96%
“…In the elderly female residents, they reported that the urinary 8-OHdG levels tended to decrease with time after the disasters (31). Conversely, Borovac Stefanovic et al, (32) did not find an association between serum MDA levels and PTSD. Ceprnja et al, examined oxidative damage markers in PTSD patients.…”
Section: Discussionmentioning
confidence: 88%
“…The reports in the literature about oxidative stress levels in patients with PTSD are controversial (16,31,32). Attari et al,(16) reported increased MDA levels in patients with PTSD compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%